2018
DOI: 10.1002/adfm.201800512
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Wurtzite GaSb Using InAs Nanowire Templates

Abstract: The crystal structure of a material has a large impact on the electronic and material properties such as band alignment, bandgap energy, and surface energies. Au-seeded III-V nanowires are promising structures for exploring these effects, since for most III-V materials they readily grow in either wurtzite or zinc blende crystal structure. In III-Sb nanowires however, wurtzite crystal structure growth has proven difficult. Therefore, other methods must be developed to achieve wurtzite antimonides. For GaSb, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…In the same study, Namazi et al have shown that the reverse transition from GaSb to InAs has identical properties. The same InGaAs ternary material emerges at the GaSb-InAs radial heterointerface in wurtzite InAs-GaSb-InAs core-shell-shell structure [71]. In the last example we present a radial/axial zinc-blende GaSb-InAs heterostructure nanowire system, where the interfaces have been identified by atomic-resolution spectrum imaging of core-loss EELS chemical signals.…”
Section: Heterojunctionsmentioning
confidence: 92%
“…In the same study, Namazi et al have shown that the reverse transition from GaSb to InAs has identical properties. The same InGaAs ternary material emerges at the GaSb-InAs radial heterointerface in wurtzite InAs-GaSb-InAs core-shell-shell structure [71]. In the last example we present a radial/axial zinc-blende GaSb-InAs heterostructure nanowire system, where the interfaces have been identified by atomic-resolution spectrum imaging of core-loss EELS chemical signals.…”
Section: Heterojunctionsmentioning
confidence: 92%
“…Here we exploit the capabilities of monochromated VEELS in order to study on the nanometer scale the electronic band structure of a complex heterostructure as schematically shown in Figure 1. The figure depicts the electron trajectory of the electron beam from the electron gun, passing through the monochromator and being energy-filtered by a narrow slit, and then interacting with the specimen, which in this case is a wurtzite InAs-GaSb core-shell nanowire with the shell covering half of the core and leaving a bare wurtzite InAs segment, then followed by an axial zinc-blende GaSb segment [ 10 ]. An important advantage of such a complex nanostructure is the availability of materials with known properties (on the same specimen with similar conditions, e.g.…”
Section: Main Textmentioning
confidence: 99%
“…*** Fig. 1a shows an overview HAADF-STEM image of the InAs-GaSb heterostructure nanowires which were grown by metal-organic vapor-phase epitaxy (MOVPE) as described in ref [10]. The lower segment of the nanowire is a partial radial heterostructured nanowire consisting of a wurtzite InAs core (red in Fig.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] Having benefited from the narrow bandgap and superior hole mobility, GaSb NWs have gained many attentions in the fields of optoelectronics and electronics in the past decades. [10][11][12][13][14][15][16][17] One of the key issues affecting the practical applications is the contact barrier between GaSb NWs and metal electrodes, which is generally dependent on the work function of the used metals. [18] However, this important barrier becomes independent of the used metals in GaSb NWs based functional devices, owing to the famous surface Fermi level pinning effect.…”
Section: Introductionmentioning
confidence: 99%